Chelated Minerals, Vitamins, and Electrolytes Improve Early Production Performance and Profitability of Broiler Chickens - Ybañez, N.; Imlan, J. C. (Tropical Animal Science Journal, 2026)
Feed costs account for over half of total production costs in broiler farming; thus, minimizing them without compromising performance is essential. This study aimed to evaluate the effects of dietary feed additives containing zinc and manganese chelates, vitamins C and D, and sodium bicarbonate (NaHCO₃) on growth performance, carcass traits, and footpad dermatitis, and to conduct a cost-benefit analysis. A total of 144 male day-old Cobb 500 broiler chicks were randomly assigned to a completely randomized design (CRD) with four treatments, each replicated four times with nine birds per replicate. The dietary treatments consist of a basal diet without any additive (T1) and the basal diet supplemented with the feed additive at three inclusion levels: 0.5 g/kg (T2), 1 g/kg (T3), and 2 g/kg (T4). These inclusion levels supplied with 5, 10, and 20 mg/kg of chelated Zn and Mn; 424.5, 849, and 1,698 mg/kg of sodium bicarbonate; 4, 8, and 16 mg/kg of vitamin C; and up to 325, 650, and 1,300 IU/kg of vitamin D, respectively. The results showed that supplementing the basal diet with 2 g of Zn and Mn chelates, vitamins C and D, and a NaHCO₃ mixture per kg significantly enhanced broiler performance, especially in body weight, feed intake, and weight gain during the second week. Clear linear effects appeared in the early production stages. Additionally, a cost-benefit analysis indicated that higher supplementation was economically beneficial. Furthermore, no adverse effects were observed on carcass characteristics, skin tearing, or footpad dermatitis. In conclusion, increased supplementation with these nutrients improved broiler chicken performance during the early production phase.